Optimal level of government debt - matching wealth inequality and the fiscal sector - Edgar Vogel (European Central Bank (ECB), 2014)
We calibrate an incomplete markets large scale OLG model to the US income and wealth distribution and examine the effects of alternative government debt levels and adjustment policies on macroeconomic aggregates and welfare. We find that the government should hold negative debt. Due to the high degree of wealth and income dispersion ex ante lifetime utility increases with increasing wages (falling interest rates) by around 6% of lifetime consumption at optimal debt levels. The optimal level depends on the adjustment policy can vary by up to 70% of GDP (between -180% and -110%). With lower government debt, high income/wealth agents are always worse off. Adjusting transfers benefits the lowest income/wealth group. The largest gains are, however, experienced by agents in the middle of the income/wealth distribution: they benefit from higher wages and transfers but do not lose too much capital income.
Keywords: C54; D52; D6; E2; H2; H6; 330; Government debt; incomplete markets; redistribution; ricardian equivalence